Post-acute COVID-19 syndrome and its prolonged effects: An updated systematic review. (August 2022) - Almas, Talal; Malik, Jahanzeb; Alsubai, Abdulla K.; Jawad Zaidi, Syed Muhammad; Iqbal, Raafe; Khan, Kashif; Ali, Muhammad; Ishaq, Uzma; Alsufyani, Majid; Hadeed, Sebastian; Alsufyani, Reema; Ahmed, Reema; et al.
Abstract: Objective: This systematic review aimed at estimating the prevalence of post-acute COVID-19 symptoms in view of published literature that studied prolonged clinical manifestations after recovery from acute COVID-19 infection. Methods: Relevant databases were searched for extraction of articles. For data synthesis, based on the distribution of quantitative variables, they were expressed as mean ± standard deviation (SD) or median and interquartile range (IQR). Qualitative variables were presented as frequency (n) and percentages (%). Results: Twenty-one articles qualified for the final analysis. The most common persistent clinical manifestations were fatigue (54.11%), dyspnea (24.38%), alopecia (23.21%), hyperhidrosis (23.6%), insomnia (25.98%), anxiety (17.29%), and arthralgia (16.35%). In addition to these symptoms, new-onset hypertension, diabetes, neuropsychiatric disorders, and bladder incontinence were also reported. Conclusion: Clinical features of post-acute COVID-19 infection can manifest even after 60 days of initial infection. Multidisciplinary care along with regular follow-up must be provided to such patients. Highlights: Clinical features of post-acute COVID-19 infection can manifest even after 60 days of initial infection. Prolonged symptoms and signs are being reported in observational studies and case reports every day. Although such symptoms are usually experienced in survivors of critical illness, the post-acute effects of COVID-19 are equally being reported in patients with mild severity of disease who do not require hospitalization. Necessary future research includes stratification of these post-acute effects with gender, age, and comorbid conditions in acute, subacute, and chronic phases of the disease.